Perbandingan Kepadatan Mineral Tulang Antar Pemakai Kontrasepsi Hormonal Progestin dan Kontrasepsi Non Hormonal pada Wanita Usia Subur - Aprilina Aprilina; Wiryawan Permadi; Elsa Pudji Setyawati; Farid Husin; Johanes C. Mose; Yudi Mulyana Hidayat (Jurnal Kesehatan, 2020)
The decrease of bone mineral density will result in reducing bone strength tend to bone brittle so osteoporosis occurred. Osteoporosis affects 44 million people in the United States, 80% are women. It was assumed that progestin contraceptive acceptors decreased bone mineral density and increased the risk of osteoporotic fractures. The study used a comparative analytical method by using a cross-sectional study. The population was all acceptors progestin hormonal contraceptives (implants or injections) and acceptors of non-hormonal contraception (IUD or MOW) who came to the Public health center of Sekip Palembang and public health center of Basuki Rahmat in Palembang. The total sample was 200 respondents. The sample used purposive sampling, by using a consecutive sampling technique. The results were analyzed by using the Mann Whitney test and two ways ANOVA test directions with post hoc test and profile analysis. The results showed a significant difference in bone mineral density between the acceptors of progestin hormonal contraceptives and the acceptors of non- hormonal contraceptives to eligible women with ρ-value=0.001. There was a significant difference between acceptor of progestin hormonal contraceptives and non- hormonal contraceptives to eligible women referred to the duration of use, p-value of 1-2 years old was p-value=0.109, >2-3 years, p-value 0.039, and ≥3 years, p-value=0.033. Conclusion: there are differences in bone mineral density between acceptors of progestin hormonal contraceptives and acceptors of non-hormonal contraceptives to eligible women.